Negara, Brexit, dan Media Massa: Sebuah Komunikasi Politik Pemerintah Inggris - Febriyan, Muhammad Alvin; Fadlillah, Fandhy Maulana; Tessalonika, Thania; Bella, Fatma (Global and Policy Journal of International Relations, 2022)
ABSTRACTThe United Kingdom was hit by a long history of political phenomena, in which the BritishGovernment held a referendum on British Exit (Brexit) in 2016. This is related to the m any pros andcons of the Brexit issu e which has formed two camps, namely the pr o camp is called "Vote Leave"and the contra camp is called "Vote Remain". The purpose of this study is to find out: (1) To find outthat the campaign is political communication for politicians; (2) To determine t he correlation androle of the mass media a s a medium of communication in delivering the campaign . Given this issue,British political figures played their role by carrying out their political communications to attractp ublic attention by carrying out camp aigns using the mass media. The increase in people choosingor becoming pro Brexit cannot be separated from the role of the mass media, for example the printmedia of the Daily Mail newspaper. The newspaper, which is in the pro camp, emphasizes wordsagain st immigrants and the economy so that peopl e become a port of this Brexit.Keywords:Brexit, Mass Media, Campaign, Daily Mail, CommunicationDOI: https://doi.org/10.33005/jgp.v10i02.3750